Plastome evolution in the East Asian lobelias (Lobelioideae) using phylogenomic and comparative analyses - Li, Chun-Jiao; Xie, Xin-Tong; Liu, Hong-Xin; Wang, Ruo-Nan; Li, De-Zhu (Frontiers in Plant Science, 2023)
Lobelia species, as rich source of the alkaloid lobeline which has been shown to have important biological activity, have been used in folk medicine throughout East Asia to treat various diseases. However, Lobelia is a complex and varied genus in East Asia and is thus difficult to identify. Genomic resources would aid identification, however the availability of such information is poor, preventing a clear understanding of their evolutionary history from being established. To close this gap in the available genomic data, in this study, 17 plastomes of East Asian lobelias were newly sequenced and assembled. Although the plastomes of Lobelia sect. Hypsela, L. sect. Speirema, and L. sect. Rhynchopetalum shared the gene structure, the inverted repeat (IR)/large single copy (LSC) boundaries, genome size, and the number of repeats were variable, indicating the non-conservative nature of plastome evolution within these sections. However, the genomes of the Lobelia sect. Delostemon and L. sect. Stenotium showed rearrangements, revealing that these two sections might have undergone different evolutionary histories. We assessed nine hotspot genes and 27-51 simple sequence repeat motifs, which will also serve as valuable DNA barcode regions in future population genetics studies and for the delineation of plant species. Our phylogenetic analysis resolved the evolutionary positions of the five sections in agreement with previous evolutionary trees based on morphological features. Although phylogenetic reconstruction of Lobelioideae based on the rpoC2 gene has rarely been performed, our results indicated that it contains a considerable amount of phylogenetic information and offers great promise for further phylogenetic analysis of Lobelioideae. Our site-specific model identified 173 sites under highly positive selections. The branch-site model exhibited 11 positive selection sites involving four genes in the East Asian branches. These four genes may play critical roles in the adaptation of East Asian taxa to diverse environments. Our study is the first to detect plastome organization, phylogenetic utility, and signatures of positive selection in the plastomes of East Asian lobelias, which will help to further advance taxonomic and evolutionary studies and the utilization of medicinal plant resources.